Evaluasi Pembelajaran Kimia Kelas XI di SMA Negeri 1 Lueng Putu Tahun Ajaran 2017/2018 - Muhammad Muhammad (Center for Research and Community Service (LPPM) University of Abulyatama, 2018)
The aims of this research are to know and to evaluate the process of Chemistry learning activities in high school. The research conducted on teachers (educators), students at SMA Negeri 1 Lueng Putu by giving questionnaires, observations and interviews. Learning is the most basic activity in the school so that the success or failure of the achievement of educational goals depends on how the learning process. It is expected to be a serious and maximum performance and supported by completing the inadequate infrastructure facilities. Based on the result of the students’ questionnaire, it found that the learning process of Chemistry activity was still not maximal. The population was all the students of class XI SMA Negeri 1 Lueng Putu which amounted to 3 classes. The sample used in this study was only 2 classes, where each class consisted of 40 students. Based on the result of questionnaire tabulation, it found that the learning process that was applied by teacher (educator) was 81,16% (good), and how the students’ learning was 66,78% (enough). Based on the results of observations on the schools, it found that the laboratories and libraries are not functioning. The results of interviews on teachers stated the use of less than the maximum media and student learning equipment is less complete. By looking at the learning process in schools, especially Chemistry less than the maximum, so it is needed to be improved to achieve the good results.